Renin-Angiotensin System Responds to Prolonged Hypotensive Effect Induced by Mandibular Extension in Spontaneously Hypertensive Rats - Sabatino, Laura; Costagli, Chiara; Lapi, Dominga; Del Seppia, Cristina; Federighi, Giuseppe; Balzan, Silvana; Colantuoni, Antonio; Iervasi, Giorgio; Scuri, Rossana (Frontiers in Physiology, 2018)
There is an ongoing interest in the renin-angiotensin system (RAS) contribution either to pathological mechanisms leading to hypertension (mainly regarding the ACE/AngII/AT1R axis), or, to RAS protective and pro-regenerative actions, primarily ascribed to the mediation of the AT2R and the MAS1 receptor. In the present study, we evaluated the modulation of gene expression and protein levels of “deleterious” (ACE/AngII/AT1R) and “protective” (ACE/AngII/AT2R and ACE2/Ang(1-7)/MAS1) arms) RAS components in parietal and frontal areas of cerebral cortex of spontaneously hypertensive rats (SHRs), after two periods of mandibular extensions (MEs). Blood pressure, BP and heart rate, HR were also measured. While no significant changes in BP and HR were present in the sham operated (SO) group, in rats after two MEs (2-ME rats), BP displayed a marked decrease (p<0.001) at ME2, and remained then stably low for the subsequent observation period. In gene expression analysis, in SHRs undergoing two MEs, either in parietal or frontal cortex, we did not observe any significant variation of AT2R and ACE2 with respect to SO rats. In contrast, we observed a decrease in Mas1 gene expression in parietal area (p<0.01) and an increase in frontal region (p<0.01). AT1R and ACE gene expression was significantly higher in 2-ME rats than SO in parietal cortex (p<0.05) but no difference was observed in the frontal area. Concerning protein levels, in parietal area, AT1R and AT2R did not change whereas MAS1 significantly decreased in 2-ME rats (p<0.05). In frontal area, both AT1R and AT2R significantly decreased in 2-ME rats (p<0.05), whereas MAS1 did not significantly change. Gene expression analysis in normotensive (NT) rats revealed the non-detectability of AT1R in both parietal and frontal zone. In parietal area, AT2R (p<0.0001) and Mas1 (p<0.01) were significantly increased in SO NT compared to 2-ME, and ACE and ACE2 resulted not detectable whereas there was some expression of these genes after 2-ME procedure. In conclusion, our data in rat models indicated that a 2-ME procedure induced a hypotensive response and that a modulation of gene expression and protein levels of RAS components occurred in different cerebral cortex areas.